The physical, mental, moral and spiritual value of a study of home economics - Streeter, Annie Louisa (My University, 1899)
Introduction: “If the national life depends on the state, and the state depends on the homes of its people, we can clearly see that the first and primary responsibility rests upon the foundation-the home-maker and house-keeper” Civil government teaches us that a nation never rises any higher than the homes of its people; Therefore, if we are to become a nation strong physically, mentally, morally and spiritually, our homes must meet all these elements of growth. As all life is subject to the law of environment, the home must be surrounded by all the pure, healthful and practical environments necessary to its complete and perfect growth. Our education must also be surrounded by the same conditions, for true education means all that pertains to the development of body mind and soul.”
Citation: Streeter, Annie Louisa. The physical, mental, moral and spiritual value of a study of home economics. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Domestic Science; Domestic Art; Home Ethics; Theses; Manuscripts (documents)